Stable thyroid function despite regular use of povidone-iodine throat spray for SARS-CoV-2 prophylaxis. (31st December 2022) - Quek, Amy May Lin; Ng, Mei Yen; Teng, Ooiean; Lim, Nicole-Ann; Ng, Geelyn Jeng Lin; Yang, Samantha Peiling; Hartman, Mikael; Tambyah, Paul Anantharajah; Cook, Alex R.; Seet, Raymond Chee Seong
Abstract: Background: It is unclear whether unintentional ingestion of povidone-iodine following its application to the oropharyngeal space could affect thyroid function. Objective: To examine thyroid function among individuals who regularly apply povidone-iodine throat spray for SARS-CoV-2 prophylaxis. Methods: We designed a case-control study to compare thyroid function among participants who received povidone-iodine throat spray three times a day for 42 days ('cases') and those who received vitamin C ('controls'). Thyroid function was assessed by profiling serum TSH, free T3, and free T4; iodine status was estimated using serum thyroglobulin level, while infection status was determined by measuring anti-SARS-CoV-2 antibody against the nucleocapsid antigen. All measurements were performed in pairs, at baseline and 42 days later. Pre-post changes in thyroid function were compared between groups, before and after stratification according to baseline TSH quartiles. Results: A total of 177 men (117 cases and 60 controls) (mean age, 32.2 years) were included. Despite comparable demographics and clinical profiles, no clinically or statistically significant differences were observed in thyroid indices between 'cases' and 'controls' before and after stratification according to TSH quartiles. None of the participants developed symptomatic hypo- or hyperthyroidism throughout the study. Post-hoc analysis did not reveal differences in thyroid function according to infection status. Conclusions: Data from this study support the overall safety of povidone-iodine use in the oropharyngeal space for SARS-CoV-2 prophylaxis among individuals with normal thyroid function and subclinical thyroid disease.